2018
DOI: 10.1021/acs.analchem.8b02356
|View full text |Cite
|
Sign up to set email alerts
|

FDM 3D Printing of High-Pressure, Heat-Resistant, Transparent Microfluidic Devices

Abstract: Transparent surfaces within microfluidic devices are essential for accurate quantification of chemical, biological, and mechanical interactions. Here, we report how to create low-cost, rapid 3D-printed microfluidic devices that are optically free from artifacts and have transparent surfaces suitable for visualizing a variety of fluid phenomenon. The methodology described here can be used for creating high-pressure microfluidic systems (significantly higher than PDMS-glass bonding). We develop methods for annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 28 publications
1
83
0
2
Order By: Relevance
“…However, it is a popular material used in AM and has been proven to be effective in FDM [56]. A study on microfluidic devices has shown the use of PLA through FDM to manufacture medical devices, with less than 1% variability shown between replicate prints [69]. PLA stents have also been produced through FDM, with a printing temperature of 220 • C [70].…”
Section: Poly(lactic Acid)mentioning
confidence: 99%
“…However, it is a popular material used in AM and has been proven to be effective in FDM [56]. A study on microfluidic devices has shown the use of PLA through FDM to manufacture medical devices, with less than 1% variability shown between replicate prints [69]. PLA stents have also been produced through FDM, with a printing temperature of 220 • C [70].…”
Section: Poly(lactic Acid)mentioning
confidence: 99%
“…Unless these parameters can be reversed, it seems likely that the next generation of devices will be engineered using 2-photon lithography and/or additive manufacturing. Alongside the drive for optical transparency, which is already becoming a mainstream demand for devices, 73,74 the critical features that will drive the development of this technology for bottom-up synthetic biology are; Resolution: The size of bilayer encased compartments that can be engineered on-chip is directly related to the dimensions of the microchannels. This combined with growing interest in constructing multicompartment and networked model assemblies at biorepresentative length-scales, places huge emphasis on resolution when fabricating RP devices.…”
Section: Future Perspectivementioning
confidence: 99%
“…На процесс печати влияют многие факторы, такие как длительность печати, посторонние тепловые воздействия на объект печати и на само устройство и т.д. Проанализировав выводы Romanov [6] , Sun [8] и Wang [9], принимаем за исходное, что процесс протекает одинаково в плоскостях l1, l2, l3 при рекомендованной скорости печати.…”
Section: рис 5 таблица с температурными режимами экспериментовunclassified